Optimalisasi Pemeriksaan Kreatinin dan eGFR sebagai Indikator Biomarker untuk Deteksi Dini Penyakit Ginjal - Sari, Triyana; Santoso, Alexander Halim; Wijaya, Bryan Anna; Enike, Syilvia Cendy; Khoto, Anthon Eka Prayoga (PT. Riset Press International, 2026)
Chronic kidney disease (CKD) is a growing global health issue, particularly among the elderly, as it progresses silently and often remains undetected until advanced stages. Early identification is essential to slow the deterioration of kidney function and reduce cardiovascular complications. This community engagement program aimed to optimize serum creatinine testing and estimated glomerular filtration rate (eGFR) calculation as simple yet reliable biomarkers for CKD screening. A total of 99 participants (mean age 71.85 ± 8.08 years) underwent laboratory assessments and health education. The mean creatinine level was 1.41 mg/dL, with an average eGFR of 53.14 mL/min/1.73 m²; most participants (55.6%) fell within the moderate impairment category. Based on KDIGO criteria, only 1% had normal kidney function, whereas 5.1% had reached end-stage renal disease. Age, cardiometabolic factors, and sex differences were associated with varying degrees of dysfunction. Combining biomarker screening with education effectively increased awareness and supported community health workers. Serum creatinine and eGFR assessment are recommended as promotive-preventive strategies for early CKD detection in high-risk populations.